Profil kemampuan guru sekolah dasar benguet filipina dalam menganalisis soal HOT (Higher Order Thinking) materi IPA - Rista Tiana; Idam Ragil Widianto Atmojo; Karsono Karsono (Universitas Sebelas Maret, 2019)
The purpose of this research was to analyze the ability of profile teachers from elementary schools. The subjects were 14 teachers taken from all the teachers in Elementary Laboratory School of Benguet State University in Philippines. This was a mix methode of qualitative and quantitative research. The instrument used had 15 items with HOT Levels that were comprised of C4 (Analyze) represented in 5 items, C5 (Evaluate) referring to 5 items, and C6 (Create) referring to 5 items. The result of teacher’s ability to analyze is showed by two category, there are: 1) the category based the subject of teachers, and 2) the category based on the item object questions. The level that could be analyzed by the teachers with the highest percentage of 93,33%. Meanwhile, the lowest percentage that could be analyzed by teachers is 33,33%. While the category based on the object items in C4 level is 77,51%, in C5 level is 58,94%, and in C6 level is 67,41%. Based on the result, it could be concluded that in analyzing HOT questions the ELS teachers could analyze the questions correctly, the ELS’s teachers were classified in the good category in analyzing the HOT science questions.Keywords: HOT (Higher Order Thinking), analyze questions, teachers, and elementary laboratory school